Childhood Hodgkin International Prognostic Score (CHIPS) Predicts event‐free survival in Hodgkin Lymphoma: A Report from the Children's Oncology Group. Issue 4 (27th October 2016) - Schwartz, Cindy L.; Chen, Lu; McCarten, Kathleen; Wolden, Suzanne; Constine, Louis S.; Hutchison, Robert E.; de Alarcon, Pedro A.; Keller, Frank G.; Kelly, Kara M.; Trippet, Tanya A.; Voss, Stephan D.; Friedman, Debra L.
Abstract: Background: Early response to initial chemotherapy in Hodgkin lymphoma (HL) measured by computed tomography (CT) and/or positron emission tomography (PET) after two to three cycles of chemotherapy may inform therapeutic decisions. Risk stratification at diagnosis could, however, allow earlier and potentially more efficacious treatment modifications. Patients and Methods: We developed a predictive model for event‐free survival (EFS) in pediatric/adolescent HL using clinical data known at diagnosis from 1103 intermediate‐risk HL patients treated on Children's Oncology Group protocol AHOD0031 with doxorubicin, bleomycin, vincristine, etoposide, prednisone, cyclophosphamide (ABVE‐PC) chemotherapy and radiation. Independent predictors of EFS were identified and used to develop and validate a prognostic score (Childhood Hodgkin International Prognostic Score [CHIPS]). A training cohort was randomly selected to include approximately half of the overall cohort, with the remainder forming the validation cohort. Results: Stage 4 disease, large mediastinal mass, albumin (<3.5), and fever were independent predictors of EFS that were each assigned one point in the CHIPS. Four‐year EFS was 93.1% for patients with CHIPS = 0, 88.5% for patients with CHIPS = 1, 77.6% for patients with CHIPS = 2, and 69.2% for patients with CHIPS = 3. Conclusions: CHIPS was highly predictive of EFS, identifying a subset (with CHIPS 2 or 3) that comprises 27% of intermediate‐risk patients who have a 4‐year EFS of <80% and who may benefit from early therapeutic augmentation. Furthermore, CHIPS identified higher risk patients who were not identified by early PET or CT response. CHIPS is a robust and inexpensive approach to predicting risk in patients with intermediate‐risk HL that may improve ability to tailor therapy to risk factors known at diagnosis.